Modeling the distribution of the endemic Turkish moss species Cinclidotus bistratosus Kürschner & Lüb.-Nestle (Pottiaceae) under various climate change scenarios - Abay, Gökhan; Gül, Serkan (Frontiers in Plant Science, 2025)
The extant literature on the subject is inconclusive, with only a paucity of studies addressing variations in the distribution patterns of moss species, particularly those with restricted distributions, in the framework of climate change. Consequently, we constructed simulated current and predicted prospective potential distribution models of Cinclidotus bistratosus, a narrow-range endemic moss species belonging to Türkiye, using the CMCC-ESM2, HadGem3-GC31-LL, and MIROC6 climate models. The purpose of this paper is to examine the distinct habitat requirements of the endemic moss, the key environmental factors that influence its distribution, and the distribution changes of the species under climate change over a substantial spatial-temporal scale (between the periods 2021-2100). Precipitation of driest, hottest and coldest quarters has been identified as a key factor influencing C. bistratosus distribution models. The findings of this study indicate that the highest probability of habitat suitability for C. bistratosus is currently in the coastal regions of western and southern Türkiye. However, future projections indicate a substantial decline in suitable habitats and a potential expansion towards northern regions of the country. In the scenario of prospective climate warming, the appropriate habitat of C. bistratosus may shift towards northern and high-altitude regions under the SSP5-8.5 climate scenario. However, the species will not entirely withdrawal from the Mediterranean distribution range, and its possible distribution will be restricted in Türkiye. The present study provides significant information and support for understanding the effects of climate change on the distribution of C. bistratosus, as well as its future distribution and conservation strategies.